Additional Magnetic Field of Dual-parallel Rotor Permanent Magnet Synchronous Motor and Its Influence on Electromagnetic Torque - Yang Chen; Dajun Tao; Baojun Ge (CES Transactions on Electrical Machines and Systems)
The coupling effect of dual-parallel rotor connected stator permanent magnet synchronous motor not only affects the magnetic field in the coupling area, but also generates an additional magnetic field in the uncoupled area. The characteristics of the additional magnetic field and its influence on electromagnetic torque are studied in this paper. The topology and parameters of motor are described briefly. The existence of additional magnetic field is proved by the simulation models under two boundary conditions, and its characteristics and source are analyzed. The analytical model is established, and the influence of key parameters on the additional magnetic field is discussed. On this basis, the influence of the additional magnetic field on the electromagnetic torque of the motor is studied, and the analytical expression of the additional torque is constructed. The fluctuation rule is analyzed, and the additional magnetic field separation model is proposed. The theoretical analysis and simulation results reveal and improve the internal mechanism of reducing motor torque ripple by optimizing the duty angle and coupling distance. Finally, a prototype test platform is built to verify the correctness of the proposed theory and the accuracy of the simulation model.